THE ROLE AND PLACE OF COMBINED SUBSTANCES IN BASIC THERAPY OF MODERATE-SEVERITY ASTHMA IN CHILDREN - V.V. Mescheryakov; E.L. Titova (Union of pediatricians of Russia, 2011)
The article reviews the adequate selection of basic therapy for medium-severity asthma in children, analyses existing practical approaches and provides results of research to optimise the pattern of prescribing combined preparations, presents a developed objective clinical and functional adequacy criterion of combined therapy and parameters to put the patient on inflammatory mono-therapy through monitoring of bronchial obstruction reversal.Key words: asthma, treatment, children.